A Screening Tool to Identify Spasticity in Need of Treatment. (May 2017) - Zorowitz, Richard D.; Wein, Theodore H.; Dunning, Kari; Deltombe, Thierry; Olver, John H.; Davé, Shashank J.; Dimyan, Michael A.; Kelemen, John; Pagan, Fernando L.; Evans, Christopher J.; Gillard, Patrick J.; Kissela, Brett M.
Abstract : Objective: To develop a clinically useful patient-reported screening tool for health care providers to identify patients with spasticity in need of treatment regardless of etiology. Design: Eleven spasticity experts participated in a modified Delphi panel and reviewed and revised 2 iterations of a screening tool designed to identify spasticity symptoms and impact on daily function and sleep. Spasticity expert panelists evaluated items pooled from existing questionnaires to gain consensus on the screening tool content. The study also included cognitive interviews of 20 patients with varying spasticity etiologies to determine if the draft screening tool was understandable and relevant to patients with spasticity. Results: The Delphi panel reached an initial consensus on 21 of 47 items for the screening tool and determined that the tool should have no more than 11 to 15 items and a 1-month recall period for symptom and impact items. After 2 rounds of review, 13 items were selected and modified by the expert panelists. Most patients (n = 16 [80%]) completed the cognitive interview and interpreted the items as intended. Conclusions: Through the use of a Delphi panel and patient interviews, a 13-item spasticity screening tool was developed that will be practical and easy to use in routine clinical practice.